Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Dengan Komitmen Organisasi Sebagai Variabel Pemoderasi - Ricka Moersiya; Tun Huseno (CV. ITTC INDONESIA, 2022)
This study aims to identify and analyze the factors that influence the quality of financial reports in local governments, with organizational commitment as a moderating variable. The population in this study were officials/employees who were directly involved in the administration and financial reporting of 44 SKPD in Agam Regency, namely 159 people. The sampling technique used purposive sampling technique by selecting 3 employees in each SKPD, namely the head of SKPD, PPK SKPD and treasurer. This research design is quantitative with an associative approach. Data collection techniques using a questionnaire. Data analysis was performed with Smart PLS regression analysis. The results showed that (1) HR competence had a positive and insignificant effect on the quality of financial reports, (2) Internal Control Systems (SPI) had a positive and significant effect on the quality of financial reports, (3) Information Technology had a negative and insignificant effect on the quality of financial reports, (4) Data Reconciliation had a negative and insignificant effect on the quality of financial reports, (5) Organizational Commitment had a positive and significant effect on the quality of Financial Statements, (6) Organizational Commitment was not able to strengthen or support the influence of human resource competence on financial report quality, (7) Organizational Commitment did not strengthen or support the influence of the Internal Control System on quality of Financial Reports, (8) Organizational Commitment does not strengthen or support the influence of Information Technology on the Quality of Financial Statements, and (9) Organizational Commitment does not strengthen or support the effect of Data Reconciliation on the Quality of Financial Statements.